A study on the key factors in influencing stock market return / Nuridayu Parman - Parman, Nuridayu (2015)
This study empirically examines the ability of the key factors (liquidity, firm size, and price to earning ratio) in explaining panel data of stock return in the Malaysia. Kuala Lumpur Stock Exchange (KLSE) data and others data had been used as a secondary data of research. The sample consisted of 6 issuing companies of Kuala Lumpur Stock Exchange (KLSE) were randomly selected on yearly basis spanning from 2010 to 2014. Several tests with the purpose of this research, we estimated a Random Effect, Fixed Effect and Pooled OLS. However, consistent with previous researchers where are still debating the factors towards stock return. Hence, the expected outcome from the regression analysis determines whether the key factors could be influenced towards stock return during the period were selected.